Batik : karya agung warisan budaya dunia - Prasetyo, Anindito ([Yogyakarta] : Pura Pustaka, 2010)
History and development of batik in Indonesia.
Includes bibliographical references (page 103-115).
Keywords: Batik -- Indonesia; Batik -- Indonesia -- History